Metabolic syndrome, physical activity and eating habits in school children of the south of Mexico City // Síndrome metabólico, actividad física y hábitos de alimentación en escolares del sur de la Ciudad de México - Rodríguez López, Carmen Paulina; Ramos-Terrones, Idalia; Lazarevich, Irina; García-López, Salvador; Villanueva Arriaga, Rosina; Figueroa Valverde, Lauro; García Cervera, Elodia; Nájera-Medina, Oralia (Investigación Clínica, 2020)
Abstract Childhood obesity has increased in recent years, due mainly to the intake of a hypercaloric diet and decreased physical activity. Obese children are more likely to have metabolic syndrome (MS). The objective of this study was to evaluate the prevalence of MS in obese (Ob), overweight (OW) and at risk of overweight (ROW) children, as well as its association with eating habits and physical activity (PA). Anthropometric measurements were made in schoolchildren in Mexico City to detect these conditions. Biochemical tests were made for the diagnosis of MS. A 24-hour dietary anamnesis on food consumption and a physical activity questionnaire were applied. We analyzed the results from 70 children, average age of 11.11 years (± 9 months); 54% were boys and 46% girls. Forty nine percent were at ROW, 43% OW and 8%Ob. Of this sample, 69% had a waist circumference above the 85th percentile. The highest prevalence of altered biochemical parameters were triglycerides and HDL-cholesterol. MS was present in 33% of schoolchildren and risk of MS in 27%. More than half of the children (57%) reported performing PA, of this group only 15% performed PA according to the WHO and presented a lower prevalence of MS, but was not statistically significant. No association was found between reported food consumption and MS. A considerable number of school children (mainly males) presented metabolic alterations, which was also related to a low level of PA. Therefore, it is important to apply preventive health measures from an early age. Resumen. La obesidad infantil ha incrementado en los últimos años, principalmente por aumento en la dieta hipercalórica y disminución de la actividad física (AF). Los niños que presentan obesidad son más propensos a padecer síndrome metabólico (SM). El objetivo de la investigación fue evaluar la prevalencia de SM en niños con riesgo de sobrepeso (RSP), sobrepeso (SP) y obesidad (Ob), así como su asociación con hábitos alimentarios y AF. Se realizaron medidas antropométricas para detectar RSP, SP y Ob; y pruebas bioquímicas para el diagnóstico de SM en escolares de la Ciudad de México. Se aplicó un recordatorio de 24 h sobre consumo de alimentos y un cuestionario de AF. Se analizaron resultados de 70 niños, con una edad de 11,11 años ± 9 meses, 54% fueron hombres y 46% mujeres. El 49% presentó RSP, el 43% SP, el 8% Ob (sólo hombres) y 69% circunferencia de cintura por arriba del percentil 85th. La mayor prevalencia de parámetros bioquímicos alterados fueron triglicéridos y HDL-c. El 33% de los escolares presentó SM y el 27% riesgo de SM. El 57% reportó realizar AF, de este grupo, sólo el 15% lo realizó de acuerdo a la OMS y fueron los que presentaron menor prevalencia de SM, sin diferencia estadística. No se encontró asociación entre el consumo de alimentos y el SM. Un número considerable de los escolares (principalmente hombres) presentó alteraciones metabólicas, lo que también se relacionó con inactividad física. Por lo tanto, es importante aplicar medidas preventivas de salud desde edades tempranas